The farming ritual and the rice metaphor: how people of Kasepuhan Sinarresmi worship rice - Ekaning Krisnawati; Eva Tuckyta Sari Sujatna; Rosaria Mita Amalia; Ypsi Soeria Soemantri; Kasno Pamungkas (Cogent Arts & Humanities)
Rice is the most important staple food in the world, and its management is therefore of vital importance. Rice management of the people of Kasepuhan Sinarresmi, Sukabumi Regency West Java, Indonesia is symbolized in cultural practices of farming. Little attention has been paid to the rice metaphor in farming rituals that reveal the cognition of people in rice management. This article, therefore, aims to elucidate the farming ritual that reveals the cognition of the people of Kasepuhan Sinarresmi in dealing with rice. With a qualitative method in nature, the data were collected from observations and interviews with the leader of the kasepuhan. Being one of the ethnicities in Indonesia, Sundanese people in Kasepuhan Sinarresmi have demonstrated their cultural practices that worship rice and its goddess, Dewi Sri. Dewi Sri is believed to provide a good life and an abundant rice crop for the people. Some research claims that cognition affects behavior, and in the same notion we argue that the cognition of the people of Kasepuhan Sinarresmi manifested and constructed in the farming ritual influences the way the people treat rice that yields in rice metaphor. Implementing this, the people of this kasepuhan manage to be self-sufficient in rice.